Continuous Cropped Winter Wheat in North Central Kansas - Warmann, Gerald W.; Dhuyvetter, Kevin C. (My University, 1995)
This publication provides estimated cost and returns for forward farm planning for continuous cropped winter wheat in north central Kansas
MF2158_1995_10
Keywords: MF2158; Crops; Economics; MF